2016
DOI: 10.1038/srep29586
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage association study to identify the genetic susceptibility of a novel common variant of rs2075290 in ZPR1 to type 2 diabetes

Abstract: The SNP of rs964184 in ZPR1 has recently been associated with type 2 diabetes mellitus (T2DM) in Japanese individuals. To comprehensively investigate the association of common variants in ZPR1 with T2DM in Han Chinese individuals, we designed a two-stage case-control study of 3,505 T2DM patients and 6,911 unrelated healthy Han Chinese individuals. A total of 24 single nucleotide polymorphisms (SNPs) were genotyped, and single-SNP association, imputation and gender-specific association analyses were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
(38 reference statements)
1
28
0
Order By: Relevance
“…The ZPR1 binds to the promoter of peroxisome proliferator-activated receptor gamma (PPARG) proteins 1 and 2, which play a key role in insulin sensitivity and obesity [86,87]. A previous study reported the evidence linking the genetic susceptibility of common variants in ZPR1 to type 2 diabetes with the levels of fasting plasma glucose and blood hemoglobin A1c, suggesting ZPR1 might be involved in abnormal glucose metabolism [88]. However, the expression tendency seems to be different in skin tissue and others.…”
Section: Alterations In Pseudogene Lncrna Rna Gene Rna Processing mentioning
confidence: 99%
“…The ZPR1 binds to the promoter of peroxisome proliferator-activated receptor gamma (PPARG) proteins 1 and 2, which play a key role in insulin sensitivity and obesity [86,87]. A previous study reported the evidence linking the genetic susceptibility of common variants in ZPR1 to type 2 diabetes with the levels of fasting plasma glucose and blood hemoglobin A1c, suggesting ZPR1 might be involved in abnormal glucose metabolism [88]. However, the expression tendency seems to be different in skin tissue and others.…”
Section: Alterations In Pseudogene Lncrna Rna Gene Rna Processing mentioning
confidence: 99%
“…With the rapid development of high-throughput sequencing, although more and more susceptibility variants of complex diseases have been identified (Guan et al, 2013(Guan et al, , 2014(Guan et al, , 2016a(Guan et al, , 2016b(Guan et al, , 2016cLiu et al, 2014;Zhang et al, 2018a). In recent years, researchers have identified strong association signals between the TLR-9 gene and the risk of KOA in both Han Chinese and Turkish populations (Su et al, 2012a;Balbaloglu et al, 2017;Zheng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we have applied some criteria to restrict the genetic background of our study subjects to minimize their genetic heterogeneity. Thus, due to the subject individuals from the same geographical area, although the potential population stratification cannot be completely excluded, our sampling strategy can effectively avoid significant population stratification to the greatest extent [37][38][39][40][41][42] . Another limitation is that this study is not a randomized clinical trial, thus selection bias might be present.…”
Section: Discussionmentioning
confidence: 99%